KEKONVERGENAN BARISAN OPERATOR SELF-ADJOINT MONOTON - Arta Ekayanti (Universitas Muhammadiyah Ponorogo, 2016)
In this paper, we discuss about monoton sequences of self-adjoint operator which bounded. By considering the commutative properties of positive operator, we prove this sequence convergence to a self-adjoint operator. Furthermore, the sequence and its limit was bounded by the same operator.Keywords: sequence, self-adjoint, monoton, convergence